Pengaruh rasio profitabilitas, leverage dan ukuran perusahaan terhadap manajemen laba pada perusahaan manufaktur yang terdaftar di BEI 2011-2018 - Fitriyah Fitriyah (Universitas Islam Lamongan, 2021)
ABSTRACTThis study aims to examine the effect of profitability ratios, leverage and company size on earnings management (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange 2011-2018). The model used in this study is panel regression using Eviews 8. The analysis method used is multiple linear analysis method. Based on the results of the study: Profitability ratios obtained with a probability value of 0.4702 > 0.05 has no effect on Profit Management. leverage is obtained with a value of 0.0452 <0.05 so that leverage has a significant positive effect on earnings management. While company size is obtained with a probability value of 0.6684 > 0.05 has no effect on earnings management. Profitability, leverage and company size are obtained with a probability value of 0.044192 <0.05, which together have a significant effect on earnings management. Keywords: Profitability Ratio, Leverage, company size and Profit Management